The Contribution of Pesantren Kilat Program to Students' Religious Knowledge and Behaviors at Elementary School - Aisy, Salwa Rihadatul; Syahidin, Syahidin; Fakhruddin, Agus (EDUCARE: Journal of Primary Education Published by Faculty of Tarbiyah and Teacher Training, Kiai Haji Achmad Siddiq State Islamic University of Jember, East Java, Indonesia, 2024)
In the context of modernization and globalization, elementary school students face challenges in preserving their understanding and practice of religious values amid the influence of external cultures. The Pesantren Kilat program at Elementary School is designed as an effective solution to strengthen students' religious knowledge and cultivate Islamic behavior from an early age. The program aims to deepen students' understanding of Islamic teachings and assist them in applying moral values in their daily lives. This study examines how the Pesantren Kilat program enhances students' religious knowledge and shapes Islamic behavior at Elementary School. Adopting a qualitative case study approach, the research explores the role of the program in enriching students' religious understanding and developing their ethics and morality based on Islamic teachings. Data were collected through observation, interviews, and documentation. The findings indicate that the Pesantren Kilat program effectively increases religious knowledge and promotes Islamic behavior in students. The program helps students internalize and apply Islamic values in daily life by integrating theoretical and practical learning. Structured activities such as interactive lessons, worship, and behavior monitoring lead to noticeable improvements in students' religious adherence and social behavior, demonstrating the program's success in fostering spiritual growth and moral development. This study's contribution is to show that the Pesantren Kilat program is effective in improving students' religious knowledge and Islamic behavior through theoretical and practical learning activities. It has become an effective model for internalizing Islamic values and promoting spiritual growth and moral development.